2023
DOI: 10.38211/joarps.2023.04.01.49
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Different Insecticides Against Lesser Date Moth, Batrachedra amydraula Meyrick, 1916 (Lepidoptera: Batrachedridae) under Field Conditions

Abstract: Abdel-Samad SSM, Adel H & Abbas MK (2019). A new strategy for controlling three devastating pests attacking date plantations in El Bahariya and Siwa oases, Egypt through using a special group of natural enemies. Egypt J of Agr Res 97(1): 365-382. Abul-Soad AA & Mahdi SM (2010). Commercial production of tissue culture date palm P. dactylifera L. by inflorescence technique. J of Gen Eng and Bio 8(2): 39-44. Addisu S, Mulugeta N, Thangavel S & Amsalu A (2022). Determination of most effective insectici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In order to mitigate the toxic effects of salt stress on plant development, containing plant genetic engineering, there are several approaches have been established (Abdela et al, 2020), and now-a-days the usage of plant growth-promoting bacteria (PGPB) (Dimkpa et al, 2009;Mastoi et al, 2023). Earlier research have been showed that application of PGPR has become an auspicious substitute to lower the salt stress produced by salts (Yeo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In order to mitigate the toxic effects of salt stress on plant development, containing plant genetic engineering, there are several approaches have been established (Abdela et al, 2020), and now-a-days the usage of plant growth-promoting bacteria (PGPB) (Dimkpa et al, 2009;Mastoi et al, 2023). Earlier research have been showed that application of PGPR has become an auspicious substitute to lower the salt stress produced by salts (Yeo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%